Nature Faith and Native Faith as Integrative Spiritualities in Hungarian Ecovillages - Farkas, Judit (Journal for the study of religion, nature and culture, 2018)
A basic assumption in contemporary research on religion is that religion is not an abstract system with 'neat' compartments, but a system that changes and adapts as human beings encounter, understand, interpret, and practice it. Within this basic understanding, religion scholar Marion Bowman has proposed the term 'integrative spirituality' to refer specifically to lifestyle choices that combine an eclectic mix of spiritual ideas and practices to produce highly personalized forms of religiosity. I argue that we can understand the spiritual life of Hungarian ecovillages through this lens. Ecovillages are 'intentional' communities, that is, village communities created with conscious efforts.